2012
DOI: 10.3354/meps09499
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community distribution in relation to environmental parameters in three aquaculture systems in a Chinese subtropical eutrophic bay

Abstract: There is concern about the impact of expanding coastal aquaculture activity, particularly in China, with the biggest aquaculture industry in the world. We conducted 3 cruises to the oyster, kelp and fish farms of the Xiangshan Bay during the winter−spring transition (02/2009), winter (01/2010) and spring (04/2010). Our aim was to explore the spatial heterogeneity of the phytoplankton community in different culture habitats and evaluate the effects of mariculture on phytoplankton. Different culture types formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 49 publications
0
22
0
2
Order By: Relevance
“…Additionally, the phytoplankton community composition response differed with large diatoms in the dry season being replaced by smaller species in the wet season. Another study in China reported significant differences in phytoplankton around fish farms compared to shellfish and kelp farms (Jiang et al 2012). Phytoplankton communities varied greatly in terms of abundance and species composition around the 3 types of farms and compared to samples from outside the farms, but interestingly the authors found no clear relationship between farm nutrient discharge and phytoplankton biomass.…”
Section: Studies Reporting Significant Increase In Primary Productionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, the phytoplankton community composition response differed with large diatoms in the dry season being replaced by smaller species in the wet season. Another study in China reported significant differences in phytoplankton around fish farms compared to shellfish and kelp farms (Jiang et al 2012). Phytoplankton communities varied greatly in terms of abundance and species composition around the 3 types of farms and compared to samples from outside the farms, but interestingly the authors found no clear relationship between farm nutrient discharge and phytoplankton biomass.…”
Section: Studies Reporting Significant Increase In Primary Productionmentioning
confidence: 95%
“…Nash et al (2005) suggested that dissolved nutrient release may affect attached macroalgae, but that if eutrophication due to aquaculture does occur, it would be at locations distant from a farm (far-field) rather than at a local scale due to dispersal of dissolved nutrients by currents. A study in China comparing nutrient levels inside and 1000 m away from fish farms found that dissolved nitrogen doubled at the farms during warmer seasons, potentially contributing to eutrophication in the area (Jiang et al 2012). Pittenger et al (2007) concluded that discharges from farms, including nitrogen, represented a significant influx of nutrients to the marine environment.…”
Section: Levels Of Nitrogen Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Plankton is een diverse groep van drijvende kleine en microscopische organismen in water die niet tegen de stroom in kunnen zwemmen. Het zeewier neemt nutriënten op en heeft zo een positief effect op de waterkwaliteit, het doorzicht in de waterkolom en de plankton diversiteit (Jiang et al, 2012).…”
Section: Samenvattingunclassified
“…Farming fish in the sea has internationally spread and although it provides plenty of marine products for human consumption, alternatively puts pressure on food supplies and ocean fisheries [5]. It should be noted that the development and excessive exploitation of aquaculture in the sea has potentially had negative environmental effects, too especially farming fish enters into the water plenty of nutrients and dietary energy sources of the fish where the local effects of fish aquaculture on the environment compared to other systems, such as seaweed or shells aquaculture is at the highest level, However, its economic interests may also be at the highest level [6]. Dense fish cages provide noticeable amounts of organic waste and inorganic solution particles [7].…”
Section: Introductionmentioning
confidence: 99%